Occurrence of Soft and Hard Ticks on Ruminants in Zagros Mountainous Areas of Iran - S Nabian; S Rahbari (Tehran University of Medical Sciences, 2008)
Background:The distribution and preferences of ticks of animals in central of Iran were studied four times a year. Methods: One thousand seven tick specimens were collected from different localities including Isfahan, Chaharmahalbakhtiary, EastAzarbaijan, West Azerbaijan, Kordestan, Kermanshah, Lorestan and Fars. Results: Most of sampled animals in this area were infested. We also encountered with a wild goat (Capra hircus aegagrus) in Kolah Qazi national park in this part that was infested intensively by Boophilus kohlsi. Fifteen ixodid tick species were identified over the study period from cattle, sheep and domestic and wild goats namely B. kohlsi (3.6%) Rhipicephalus sanguineus (4.5%), Rh.bursa (21.9%), Rh.turanicus (2.9%), Dermacentor niveus (12.9%), D.raskemensis (4.1%), D.marginatus (7.3%), Haemaphysalis punctata (3.5%), H. Parva (0.6%), H. Choldokovskyi (2%), Hyalomma anatolicum excavatum (4.8%), H.anatolicum anatolicum (5.2%), H. asiaticum asiaticum (7.3%), H. marginatum marginatum (13%), and H. detritum detritum (5.9%). The only soft tick found was Ornithodoros canestrinii which occurred in all localities of Isfahan Province but with significant differences in abundance. Clear pattern of seasonality was evident for this species and it was generally present from November to March, while ixodid ticks were present throughout the year. The largest numbers of adult ixodid ticks were generally present from April to August. Conclusion: The results showed that Rh.bursa, D.niveus and H.marginatum marginatum are dominant tick species